Combination of Sinabung Volcanic Ash and Humic Acid Against Characteristics of Humid Silica Fertilizers - Veny Apriyani; Thomson A.S Girsang; Ribka Sirait; Lisnawaty Simatupang (Universitas Negeri Medan, 2019)
Volcanic ash from Mount Sinabung has a large silica (SiO2) content of 69,93% and contains minerals needed by soil and plants. This potential cannot be directly utilized due to the acidic nature of volcanic ash which can damage plants. To be used as fertilizer, the process can be accelerated by adding humic acid from chicken manure. So the purpose of this study is to manufacture humic silica fertilizer by combining volcanic ash with humic acid from chicken manure and and the characteristics of humic silica fertilizer. In this study a method of extracting humic acid from chicken manure was used using sodium hydroxide (NaOH) 0,25 M solution and mixing volcanic ash with humic acid. The results of humic acid extract from chicken manure were then combined with volcanic ash from sinabung. Nutrients from the combination obtained at variation 60:40 with the highest organic C were 1.37%, N total 0.24%, Phosphate 20.64 ppm and Potassium 0.664 me / 100g with pH fertilizer 6 and crumb texture and free neutral which indicates the fertilizer is ready to use.